TOURISM TYPES AND MAIN VIEWS - Maxkambayeva Shaxrizoda Xusan qizi; Binoqulova Dilnora Sirojiddin qizi (Journals Park Publishing, 2023)
This article describes the increasingly developing field of tourism and its main directions, forms and types. It was also mentioned about transport services, as they are at the level of demand of tourism zones.
Keywords: tourism, swimming tourism, railway, outdoor tourism, military tourism, reserve, animals, historical buildings, traditions, values.